Experimental and numerical analysis of strengthening prestressed concrete cylinder pipes using a post-tensioning method - Zhao, Lijun; Dou, Tiesheng; Li, Chunlei; Li, Meng (Frontiers in Earth Science, 2023)
Prestress loss caused by broken wires could lead to the decline in the carrying capacity of the prestressed concrete cylinder pipes(PCCPs). The strengthening of PCCPs with post-tensioning method is becoming more and more widely utilized to restore the strengthened pipe to the design capacity to withstand the combined loads. There is no need to drain the pipe during the construction of the strengthening and this strengthening commits to actively replenish the prestress loss caused by wires breakage at a cost-effective price. To verify the strengthening effect of this method, a full-scale test and its corresponding three-dimensional finite-element model were established in this paper. A three-dimensional numerical model of three continuous prototype pipes was established accounting for the particularity of the bell and spigot. The numerical model of prestressing wires was optimized in two aspects, which was more in line with the actual situation. The spiral winding method instead of the single winding was adopted to apply prestress and the prestressing wires with a broken point were partitioned into two separate areas owning to the bond quality between the mortar coating and the wires. The simulation and the full-scale test both contain the five process of the strengthening with external prestressed strands, which is pressurized to working pressure→breaking the prestressing wires until the visible cracks propagate→gradual depressurization to artesian pressure→the tensioning operation of strands→pressurized to design pressure. The sensitivity analysis of the relating factors of the strengthening was performed through finite simulation to give better understanding of the design. The simulation results were consistent well with the data of the full-scale test, indicating that the rationality of the simulation and the full-scale test. The strengthening of PCCP with post-tensioning method is able to meet the demand of design and is a feasible strengthening method. The working pressure and the control coefficient for tensioning have the most significant impact on the strengthening effect. Technical recommendations and a better understanding for the application of the post-tensioning method on PCCP were provided in this study.